Staring at the Other: Seeing Defects in Recent Australian Poems - Jackson, Andy (Critical Disability Discourses, 2019)
When it comes to encountering the body of the other, is poetic language bound to fail? Can failure nevertheless be productive? This paper discusses four recent Australian poems which depict public encounters with bodily otherness, taking up Emmanuel Levinas’s suggestion that the other is experienced in a “defecting of disclosure”, which involves both an unsettling intimacy and a profound distance. The paper explores this paradox through two visual motifs – staring and hyperopia. When bodily otherness is encountered, this often prompts staring – which theorist Rosemary Garland Thomson sees as a site of relational and significatory potential, beginning “when ordinary seeing fails”. I argue that these poems, through the varying ways in which they stage awkward encounters with seemingly defective, disabled others, emphasise the defects in our own ability to clearly see the other. Keywords: Poetry; disability; the Other; staring, Emmanuel Levinas